Vampirina. Ghoul girls rock! [videorecording (DVD)]. - Nee, Chris (Disney DVD., 2018)
Rock out with Vampirina, Poppy, and Bridget as they take the stage and start their very own band: the Ghoul Girls! Cheer them on as they travel to Transylvania for their first-ever "Scream Factor Talent Competition". Howl with laughter when a full moon transforms much more than just Wolfie, and watch Vee make her show-stopping human ballet debut! Vamped up with awesome songs, bonus music videos and six fun-filled episodes